Mikročrpalke iz tekočekristalnih elastomerov - Janša, Nejc (Matrika, 2014)
In this paper liquid crystal elastomer micropumps are presented. For a better understanding we first study the elasticity of elastomers, starting from a simple flexible chain model. We continue by considering liquid crystals and review their structure and properties, including their response to external electric fields. Then, our focus is shifted to liquid crystal elastomers. We look at how they are constructed and learn about their reaction to external stimuli, both from a theoretical model and from experimental data. Last of all, we draw attention to the micropumps, look at how they are made and how their microscopic structure was verified. We also discuss their possible applications.
Keywords: elastomeri; elastomers; liquid crystals; micropumps; mikročrpalke; tekoči kristali